A Mathematical Model of Cerebrospinal Meningitis Epidemic: A Case Study for Jirapa District, Ghana - Wiah, Eric N.; Adetunde*, Isaac A. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
We develop a mathematical model that governs the epidemiology of cerebrospinal meningitis (CSM) in Jirapa, Ghana. For proper control to be instituted, however, the cerebrospinal meningitis and their dynamics must be known. This paper reports on the dynamics of cerebrospinal meningitis caused by bacterial infection and gives suggestions as how they can be controlled. We study the existence of a solution, the stability of equilibria, and investigate bifurcations of the system. We perform numerical simulation on the model for Jirapa District in Upper West Region of Ghana. Keywords: Mathematical Model, Cerebrospinal meningitis (CSM), Stability Analysis, Bifurcation, Respiratory Tract, Simulation. E-mail: adetunde@googlemail.com